2022
DOI: 10.3390/textiles2030022
|View full text |Cite
|
Sign up to set email alerts
|

Tight Margins: Compression Garment Use during Exercise and Recovery—A Systematic Review

Abstract: Background: Compression garments (CGs) are a popular tool that may act on physiological, physical, neuromuscular, biomechanical, and/or perceptual domains during exercise and recovery from exercise, with varying levels of efficacy. While previous reviews have focused on the effects of CGs during running, high-intensity exercise, and exercise recovery, a comprehensive systematic review that assesses the effectiveness of garment use both during and after exercise has not been recently conducted. Methods: A syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 180 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, the current meta-analytic findings are the first to report specific effects of compression sportswear on speed, endurance, and functional motor performances. Despite relatively small positive effects, the findings support a proposition that compression sportswear may improve exercise performances because of potential benefits on physiological, biomechanical, neuromuscular, and perceptual components [20].…”
Section: Discussionsupporting
confidence: 73%
“…To the best of our knowledge, the current meta-analytic findings are the first to report specific effects of compression sportswear on speed, endurance, and functional motor performances. Despite relatively small positive effects, the findings support a proposition that compression sportswear may improve exercise performances because of potential benefits on physiological, biomechanical, neuromuscular, and perceptual components [20].…”
Section: Discussionsupporting
confidence: 73%
“…Participants' nutrition, sleep environment and sleep duration were also not controlled in this study, which are potential confounding variables that influenced their recovery. It is also not well understood how repeated wear of compression garments may influence their applied pressure over time (38), which may have influenced the effect of the garments across a six-day camp. Further, the heterogeneity and size of the sample population in this pilot study should be considered in the interpretation of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Compression garments have become increasingly popular over the past decade in human performance applications, and reportedly facilitate post-exercise recovery by reducing muscle soreness, increasing blood lactate removal, and increasing perception of recovery, but the evidence is mixed, at best [16, 17,18,19,20,21]. One review study, for example, found that CGs help in recovery in terms of subsequent performance for endurance but not sprinting or jumping [22].…”
Section: Introductionmentioning
confidence: 99%